A viral protein activates the MAPK pathway to promote viral infection by downregulating callose deposition in plants - Lixiao Feng; Xiangwen Luo; Liping Huang; Yu Zhang; Fangfang Li; Shijun Li; Zhanhong Zhang; Xiao Yang; Xin Wang; Xian OuYang; Xiaobin Shi; Deyong Zhang; et al. (Nature Communications)
Abstract Mitogen-activated protein kinase (MAPK) cascades are evolutionarily conserved in both plants and animals and play critical roles in activating innate immunity to defend against various pathogens. However, the role of MAPK cascades in positively regulating or enhancing viral infections in plants is unclear. In this study, we investigate the involvement of MAPK cascades in infection by the positive-strand RNA virus tomato chlorosis virus (ToCV). Our findings reveal that ToCV infection activates MAPK cascades, promoting virus spread within plants. Specifically, ToCV P7, a pathogenicity determinant protein, localizes to the plasma membrane and recruits NbMPK3/6 from the nucleus. Subsequently, P7 is directly phosphorylated on serine 59 by NbMPK3/6. Phosphorylated P7 interacts with NbREM1.1 and inhibits its ability to induce callose deposition at plasmodesmata. These results demonstrate that NbMPK3/6 directly phosphorylate ToCV P7, modulating antiviral defence mechanisms by downregulating callose deposition at plasmodesmata and thereby enhancing ToCV transmission in N. benthamiana. This study sheds light on the intricate arms race between host defence and viral counter-defence strategies.